Collaborative healthcare information systems in privacy preservation based on K-anonymization model / Asmaa Hatem Rashid - Rashid, Asmaa Hatem (2014)
Collaboration is an important requirement in health information systems (HISs) because it produces reliable and rigorous evidence that can inform critical decisions related to healthcare services. It aids in the provision of proper and fast treatment to patients. Data privacy preservation is a crucial impediment in achieving collaboration through data sharing in line with collaborative health research through HISs. The study aims (i) to identify the factors and obstructions in technology acceptance in sharing health information among medical staff in a selected hospital in Egypt; and (ii) to determine methods to enhance data sharing based on privacy preservation among the medical staff. As a result, this study has developed a collaborative healthcare information management system (CHIMS) prototype based on the k-Anonymization model which helps to improve collaboration in the sharing of information among medical staff. The K-anonymization measures privacy preservation by generalizing data and preventing reidentification. Generalized data are extensively used in various realms, such as medical research, educational studies, and targeted marketing. In this study, data were collected from two government hospitals in Egypt as case studies. The qualitative approaches used were observation and semi-structured interviews. The semi-structured interviews were conducted with 12 participants from among the medical staff in the selected hospital. The aim of these interviews was to identify the factors that affect technology acceptance and the adoption of collaborative activities. The outcomes of these interviews are to be used to determine the requirements for the CHIMS systems. A member check was used to validate the researcher’s conclusions. Questionnaires were distributed among 60 participants comprising medical staff to evaluate the CHIMS. The results revealed that significant factors were involved, such as management, abilities and skills, culture, attitude towards technologies, and age and time. Accordingly, privacy concerns significantly affect the technology acceptance and adoption in the sharing of information among medical staff. Nonetheless, the improvement of collaboration among medical staff in data sharing based on privacy preservation in medical research similarly enhances research findings and increases the reliability of healthcare services. The CHIMS was implemented in the selected hospital to evaluate the system’s usability and effects in improving collaboration among physicians in sharing information through collaborative health research. The questionnaires method was conducted in the evaluation process. The CHIMS was found to be satisfactory as the mean level of the evaluation of the CHIMS system’s acceptance was 4.11 and the scale of Cronbach's alpha score was 0.85. These results demonstrate that the combination of sharing health data based on privacy preservation through HIS improves the collaboration among medical staff and research findings. The proposed model provides a new version of the data intended for scientific research among researchers based on the preservation of privacy; this feature was not available in the old system of the selected hospital. Further research should consider examining collaboration among the HISs of different hospitals regionally when addressing the prevention and control of diseases.